Ultrasound assessment of muscle mass in response to exercise training in chronic kidney disease: a comparison with MRI. Issue 4 (3rd May 2019) - Gould, Douglas W.; Watson, Emma L.; Wilkinson, Thomas J.; Wormleighton, Joanne; Xenophontos, Soteris; Viana, Joao L.; Smith, Alice C.
Abstract: Background: Chronic kidney disease (CKD) is a catabolic condition associated with muscle wasting and dysfunction, which associates with morbidity and mortality. There is a need for simple techniques capable of monitoring changes in muscle size with disease progression and in response to interventions aiming to increase muscle mass and function. Ultrasound is one such technique; however, it is unknown how well changes in muscle cross‐sectional area (CSA) measured using ultrasound relate to changes in whole muscle volume measured using magnetic resonance imaging. We tested whether rectus femoris CSA (RF‐CSA) could be used as a valid indication of changes in quadriceps muscle volume as a single measure of muscle size and following a 12 week exercise intervention that resulted in muscle hypertrophy. Methods: Secondary analysis of data was collected from the ExTra CKD study (ISRCTN 36489137). Quadriceps muscle size was assessed from 36 patients with non‐dialysis CKD before and after 12 weeks of supervised exercise that resulted in muscle hypertrophy. Results: Strong positive correlations were observed between RF‐CSA and quadriceps volume at baseline ( r 2 = 0.815, CI 0.661 to 0.903; P < 0.001) and following 12 week exercise ( r 2 = 0.845, CI 0.700 to 0.923; P < 0.001). A moderate positive association was also observed between changes in RF‐CSA and quadriceps following exercise training (rho = 0.441, CI 0.085 to 0.697; P = 0.015). Bland–Altman analysis revealed a small bias (bias 0.6% ± 12.5) between the mean percentage changes in RF‐CSA and quadriceps volume but wide limits of agreement from −24 to 25. Conclusions: Rectus femoris CSA appears to be a reliable index of total quadriceps volume as a simple measure of muscle size, both as a single observation and in response to exercise training in non‐dialysis CKD patients.